Heat treatment of calcium alginate films obtained by ultrasonic atomizing: physicochemical characterization - Soazo, Marina del Valle (2015)
Fil: Fil: Soazo, Marina del Valle. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR–CONICET); Argentina.